No Substitute for the Real Thing: The Importance of In-Context Field Experiments in Fundraising - Goswami, Indranil; Urminsky, Oleg (Marketing Science, 2020)
This paper is an empirical case study of fundraising decisions that examines the adequacy of various sources of guidance and demonstrates the unique importance of in-context field experiments.